Sydney's Aboriginal past : investigating the archaeological and historical records - Attenbrow, Val, 1942- (A UNSW Press book, 2010)
Revealing the diversity of Aboriginal life in the Sydney region, this study examines a variety of source documents that discuss not only Aboriginal life before colonization in 1788 but also the early years of first contact. This is the only work to explore the minutiae of Sydney Aboriginal daily life, detailing the food they ate; the tools, weapons, and equipment they used; and the beliefs, ceremonial life, and rituals they practiced. This updated edition has been revised to include recent discoveries and the analyses of the past seven years, adding yet more value to this 2004 winner of the Jo.